دور الإخطار في تفعيل الرقابة الدستورية على ضوء التعديل الدستوري لسنة 2020 - بن محـــــــمود, أحمـــد (جامعة الوادي -University eloued, 2022)
إستحدث المؤسس الدستوري الجزائري بموجب التعديل الدستوري لسنة 2020 المحكمة الدستورية ،كهيئة مستقلة وأناط بها مهمة الرقابة على دستورية القوانين وهو إتجاه صريح إلى إعتماد الرقابة القضائية و التخلي تماما عن الرقابة السياسية بواسطة المجلس الدستوري. إلا إن ممارسة المحكمة الدستوریة لوظائفها،لا سیما الوظیفة الرقابیة تتوقف على آلیة الإخطار حیث منح المؤسس الدستوري الجزائري في التعدیل الدستوري السالف الذكر سلطة إخطار المحكمة الدستوریة للعدید من الجهات والتي حددتها المادة 193 منه. بحيث تخطر المحكمة الدستورية بجمیع النصوص التشریعیة والتنظیمیة والمعاهدات والأوامر التي یصدرها رئیس الجمهوریة، ویكون إما إخطار وجوبي أو إخطار جوازي وذلك حسب نوع الرقابة المفروضة على النص حیث تتنوع الرقابة بین رقابة المطابقة ورقابة الدستوریة ورقابة توافق القوانین والتنظیمات مع المعاهدات، هذا من جهة، ومن جهة ثانیة رقابة قبلیة وجوبیة وأخرى جوازیة، ورقابة بعدیة جوازیة. إن آلية الإخطار بالدفع بعدم الدستورية، من بين الآليات الهامة التي منحها المؤسس الدستوري بموجب المادة 195 من التعديل الدستوري لسنة 2020 ، والتي يمكن من خلالها للأفراد القيام بإخطار المحكمة الدستورية بخصوص حكم تشريعي يتوقف عليه مآل الفصل في نزاع امام جهة قضائية. المؤسس الدستوري قيد آلية أو إجراء إخطار المحكمة الدستورية بعدة قيود موضوعية وشكلية بما ينعكس سلبا على دو رها الرقابي ودورها في تفسير الدستور والفصل في الخلافات بين السلطات الدستورية. بحيث يتعين توسيع هذا الإخطار إلى خارج السلطات الثلاث من خلال إضافة المؤسسات الدستورية الأخرى مثل المجلس الوطني لحقوق الانسان، المنظمات والنقابات لجهات الإخطار، وغيرها من الجهات، بقصد تفعيل دور المحكمة الدستورية في فرض حماية للدستور وحماية الحقوق والحريات المضمونة في الدستور. Under the constitutional amendment of 2020 Created the Algerian constitutional founder The Constitutional Court as an independent body And give it the task of overseeing the constitutionality of laws It is an explicit trend to adopt judicial oversight And completely abandon political control by the Constitutional Council. The Constitutional Court’s exercise of its functions, especially the supervisory function, depends on the notification mechanism, as the Algerian constitutional founder granted in the constitutional amendment in 2020 the power to notify the Constitutional Court to several bodies that were defined by، Article 193 of the amendment. as notification includes all legislative and regulatory texts, treaties and orders issued by the President The republic, and it is either a mandatory notification or a mandatory notification, depending on the type of control imposed on the text, as the censorship varies between compliance control, constitutional control, and the compliance of laws and regulations with treaties, on the one hand, and on the other hand, tribal and mandatory and other permissible control, and passive postal control. The issue of notification of unconstitutionality is among the important in Article 195 of the 2020 constitutional Amendment, which provides for notification constitutional Court to plead uncostitutional. as the constitutional founder restricted the procedure for notifying the Constitutional Court with several substantive and formal restrictions, which would negatively affect its oversight role and its role in interpreting the constitution and separation In disputes between constitutional authorities. This notification should be expanded outside the three authorities by adding other constitutional institutions such as the National Council for Human Rights, organizations and trade unions to notification agencies, and other bodies, with the aim of activating the role of the Constitutional Court in imposing protection for the constitution and protecting the rights and freedoms guaranteed in the constitution.
ماستر اداري
Keywords: : الإخطار،المحكمة الدستورية، التعديل الدستوري،الرقابة، الرقابة الدستورية،القضاء الدستوري، الإخطار،الدفع بعدم الدستورية .: Constitutional oversight, Constitutional judiciary, The Constitutional Council, payment unconstitutional، Notification،ConstitutionalCourt،constitutionalamendment، oversight